2015
DOI: 10.1016/j.kjms.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Robotic partial nephrectomy for clinical stage T1 tumors: Experience in 42 cases

Abstract: The aim of this study was to evaluate outcomes of robotic partial nephrectomy (RAPN) procedures. At two centers, 42 patients underwent RAPN. Radius, Exo/Endophytic, Nearness, Anterior/Posterior, Location (R.E.N.A.L.) nephrometry and PADUA scores of patients were calculated by computed tomography (CT) or magnetic resonance imaging (MRI). Intra- and perioperative (0-30 days) complications were evaluated using modified Clavien classification. A four-arm da Vinci-S robotic surgical system was used and outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The map scoring system was proposed in [ 3 ]. The MAP scoring system is a more comprehensive quantitative scoring method for assessing the anatomical complexity of renal tumours, which corresponds to the anatomical features of renal tumours with capital initials [ 4 ]. The variables are simple to set and relatively easy to measure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The map scoring system was proposed in [ 3 ]. The MAP scoring system is a more comprehensive quantitative scoring method for assessing the anatomical complexity of renal tumours, which corresponds to the anatomical features of renal tumours with capital initials [ 4 ]. The variables are simple to set and relatively easy to measure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, partial nephrectomy (PN) is preferred in kidney masses <4 cm, and in tumors between 4–7 cm, if suitable [ 2 ]. Previously, it has been reported that PN had similar oncologic outcomes with favorable functional outcomes compared with radical nephrectomy (RN) [ 3 ]. During robotic and laparoscopic procedures, the failure of kidney cooling is still remaining as a challenging point [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of the da Vinci robotic system (Intuitive Surgical, Sunnyvale, CA, USA), several reports showing the feasibility and safety of the procedure have been reported. [4][5][6][7][8][9][10] The utilization of the robot in this field has facilitated the PN procedure, especially during the periods of renal parenchymal dissection, renorhaphy and warm ischemia after the excision of the tumor. [11] In this study, we present our experience with robotic partial nephrectomy (RPN) in 34 patients with (n=22) and without (n=12) renal arterial clamping, and evaluate the impact of these techniques on renal functions by analyzing estimated glomerular filtration rates (eGFRs).…”
Section: Introductionmentioning
confidence: 99%